Analysis of Essential Industries and Other Fundamentals as Well As Financial Competitiveness in Driving Economic Growth in Medan City - M. Guffar Harahap; Haidir; Muhammad Hizbullah; Muhajirin Ansori Situmorang; Munawaroh; Muhammad Radian Syah; Ami Nullah Marlis Tanjung (PT FORMOSA CENDEKIA GLOBAL, 2023)
Economic growth is an indicator of economic development in the process of economic growth. The benchmark economists use to look for signs of economic growth in a country or region is regional gross domestic product (GDP). This study's goal is to evaluate which industries are included in the primary and non-primary sectors and how economic competitiveness accelerates economic growth in Medan City. This study uses quantitative research methods with class analysis tools Location Question (LQ), Shift Share and Typology.The results of the study based on the results of location inquiry analysis show that there are 12 basic sectors, namely: the field of water supply, waste treatment, waste and recycling; Construction; wholesale and retail trade, repair of cars and motorcycles; transportation and storage, provision of shelter and food; Information and Communication; financial and insurance services; Housing; business services; Education services, health services and social services and other services as well as five other economic sectors are non-core sectors of Medan City. The results of the Shift Share analysis show that almost all economic sectors in Medan City have a positive Differential Shift value, meaning that these economic sectors have strong competitiveness or high competitive advantages compared to the same industry in the Sumatran economy